PROMOSI KESEHATAN BERBASIS MASJID DALAM UPAYA UNTUK MENURUNKAN ANGKA IBU BERSALIN PADA DUKUN BAYI DI KECAMATAN BUNGARAYA KABUPATEN SIAK - M. Satria; Nofiyadi Nofiyadi (Ensiklopedia of Journal, 2018)
Health Promotion Activities are the spearhead of public health activities, technically health promotion officers directly come into contact with the community, so if health promotion or health education will not succeed, the impact will be very obvious, with increasing morbidity. Especially in matters of childbirth in addition to health workers or traditional birth attendants, until now this problem has always been one of the factors causing this problem is a health promotion factor that does not run optimally both in pregnant women or in the dukun itself. According to IDHS data the maternal mortality rate is recorded at 359/100 thousand KH and one of the causes is because mothers do not deliver with health workers. Therefore, researchers try to make the concept of mosque-based health promotion which combines the concept of health with religious beliefs to become a concept that is not only able to attract attention because it is religious but also able to have an impact on behavior because it relates to religious orders which are usually a reference many people. In this method researchers try to collaborate health material with religious material that has a correlation in preventive activities, prevention, common effort processes etc. and relate it to the role of mosques in the community which of course can always be a motor in the movement and this time will be used as a motor in the health movement especially in tackling unity problem by using non-health personnel not to mention using a large number of mosques to raise this health promotion movement. With this combination of health science and trust, it is expected to be a powerful new concept in handling health problems.The design of this study is an experiment which is one group pretest-posttest. That is testing the effectiveness of the concept of health promotion based on the handling of cases of traditional birth attendants against one group that was given intervention. With variables: Health Promotion (counseling) Based on Mosque (Extension Method, Extension Location, Eye of Counseling, Response and Behavior Change) and ChildbirthThe results of this study indicate that the overall average of mosque-based health promotion (Extension Method, Extension Location, Mataeri Extension, Response and Behavior Change) shows the number of changes and after using the T Test the P Value is obtained (0.031, 0.030, 0.010, 0.021, 0.000) with p